2019
DOI: 10.1111/vsu.13288
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic cartilage injury associated with the use of stainless‐steel cannulas and silicone‐guarded cannulas for canine stifle arthroscopy

Abstract: Objective To determine the ability to reduce iatrogenic cartilage injury (IACI) during canine stifle arthroscopy by using a silicone arthroscope cannula guard. Study design Ex vivo canine cadaver experimental study. Animals Paired canine stifles from 14 cadavers (≥20 kg). Methods Stifles (N = 28) were assigned to unguarded traditional or silicone‐guarded arthroscopy. Stifle arthroscopy and full joint exploration with meniscal probing was performed by a second‐year surgery resident (I.C.) in fourteen canine cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(87 reference statements)
1
8
0
Order By: Relevance
“…In this study, ICI occurred in all hips but the severity of lesions was considered minor in most hips. This is similar to reported ICI postarthroscopy in other joints in dogs 8,26 . Previous studies evaluating canine stifle articular cartilage ICI post arthroscopy reported a 93% incidence mostly consisting of partial thickness lesions 8,26 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this study, ICI occurred in all hips but the severity of lesions was considered minor in most hips. This is similar to reported ICI postarthroscopy in other joints in dogs 8,26 . Previous studies evaluating canine stifle articular cartilage ICI post arthroscopy reported a 93% incidence mostly consisting of partial thickness lesions 8,26 .…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to reported ICI postarthroscopy in other joints in dogs. 8,26 Previous studies evaluating canine stifle articular cartilage ICI post arthroscopy reported a 93% incidence mostly consisting of partial thickness lesions. 8,26 Arthroscopic ICI lesions can be created during portal establishment, by arthroscope cannula insertion or manipulation, by the egress needle, or while inserting or manipulating hand instruments inside the joint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Because of the extremely limited healing capacity of articular cartilage, 23,24 further studies to investigate methods to limit IACI are still warranted. 25 The current study had several limitations, including the use of cadavers, because the freeze-thaw cycle and post-mortem changes negatively affect the integrity of the articular cartilage, making IACI more likely in cadavers than in live patients. 6 On the other hand, many dogs undergoing arthroscopic surgery have some degree of intra-articular osteoarthritic cartilage, which would therefore be predisposed to injury because of softening.…”
Section: Discussionmentioning
confidence: 97%